Poem of Isa Alabi Abubakar on 11th of September Remembrance (Phonetic Morphological Study) - Abdur-Rasheed Mahmoud-Mukadam; Abdullah Akanni Shithu (University of Darussalam Gontor, 2023)
Human speech consists of successive sounds, and these sounds are interconnected and composed of groups to form words, then these words are organized into sentences and phrases to lead to a clear intended meaning from the speaker to the same listener. It is a study of the September Eleventh (11) memorial poem by the poet Isa Alabi at the phonemic and morphological levels that aims to show features and phonetic connotations in the poem and what the names of the attributes contained in it are. The study resulted that the descriptive analytical approach and came to the most important results: (1) the presence of the main syllables in the poem with the absence of secondary syllables (2) a perfect fit between sound and meaning (3) good selection of words that suit the nature of the poem (4) the names of the subject are the most frequently mentioned in the poem among the adjective